The Role of the Business Environment, Supply Chain Management and Quality Management in Improving the Competitive Advantage of Small Business Retail - I Gusti Ketut Adi Winata; Gde Agung Satria; I Putu Agus Adnyana (Universitas Pendidikan Ganesha, 2019)
The purpose of this study is to find out how to increase competitive advantage through the Business Environment, Supply Chain Management, and Quality Management in small and medium businesses in Buleleng Regency by using a quantitative approach. This research is explanatory in the form of causality between variables. In this study examines the causal relationship between the business environment, quality management, supply chain management, and the competitive advantage of Small Business Retail in Buleleng regency. Data collection used in this study used a questionnaire method. The sampling technique is done by using purposive sampling technique. The results showed the business environment, Supply Chain Management, and quality management had a positive effect on competitive advantage.